Novel radiochemistry for 18F labelled aromatics - Li, L (2011)
Positron emission tomography (PET) employs short half-life positron emitting isotopes, typically 18F, for in vivo measurement of physiological processes. Easy access to structurally diverse radiolabelled probes would accelerate the rapid progress of PET imaging but, to date, radiochemistry is still limited by cost and efficiency. Nucleophilic fluorination with 18F-fluoride is the preferred “non-carrier-added” methodology in the synthesis of 18F-labelled pharmaceuticals because it leads to radiotracers with a high specific activity, a key feature allowing for investigations to be performed in sub-toxic doses. Chapter 1 serves as an introduction on radiochemistry, especially focussing on current radiosynthetic methods for the synthesis of 18F-labelled aromatics. Aromatic compounds without electron-withdrawing groups are notoriously difficult to label with 18F-fluoride. In this thesis, we present two novel methodologies to deliver 18F-labelled aromatic compounds from nucleophilic 18F-fluoride. Chapter 2 details the experimental efforts towards “Convergent Radiosynthesis” (Scheme 1). We proposed a convergent synthetic tactic that allows for simultaneous reaction between three or more substrates, including an 18F-labelled building block. This chemistry has been validated by the radiosynthesis of various structural scaffolds which are not responsive to direct nucleophilic fluorination. Chapter 3 presents our research into “Oxidative Nucleophilic 18F-Fluorination” (Scheme 2). We proposed that electron-rich aromatics, such as phenols, which are not responsive to nucleophilic fluorination may undergo umpolung reactivity under oxidative conditions. This “umpolung strategy” allows for the direct transformation from 18F-fluoride to 4-[18F]fluorophenol. Potentially, this established oxidative fluorination strategy could be adapted to the radiosynthesis of radiotracers containing a 4-fluorophenol sub-motif, such as 6-fluoro-meta-tyrosine. An appropriate precursor has been validated for the prospective radiosynthesis of 6-[18F]fluoro-meta-tyrosine.